Pseudorabies virus triggers ferritinophagy-mediated ferroptosis and neuroinflammation in viral encephalitis - Jiali Sun; Caiyun Huo; Yuli Li; Xinsen Li; Jiawei Xu; Jijing Tian; Jin Xiao; Rui Zhang; Jun Han; Lei Zhou; Yanxin Hu; Hanchun Yang (Proceedings of the National Academy of Sciences, 2026)
Pseudorabies virus (PRV), a member of the Alphaherpesvirinae subfamily, primarily infects pigs and poses a significant threat to the swine industry. In recent years, emerging PRV variants have been reported to infect humans, predominantly causing encephalitis. Ferroptosis is a recently identified form of programmed cell death, characterized by iron-dependent lipid peroxidation. It has been implicated in the pathogenesis of various diseases, including neurodegenerative disorders and viral infections. However, whether PRV induces ferroptosis in the central nervous system and the underlying mechanisms remain to be fully elucidated. This study demonstrates that PRV infection induces ferroptosis in N2a cells, mouse primary neurons, and murine brains. Specifically, PRV infection triggers ferritinophagy in N2a cells, mouse primary neurons, and brain, increasing intracellular free iron levels and subsequent lipid peroxidation, ultimately driving ferroptosis. Furthermore, PRV-induced ferroptosis is closely associated with neuroinflammation. Mechanistically, ferroptosis upregulates prostaglandin-endoperoxide synthase 2 (PTGS2), thereby enhancing prostaglandin E 2 (PGE 2 ) synthesis and exacerbating inflammatory responses. Integrated transcriptomic and metabolomic analyses further confirm that PRV-induced ferroptosis drives neuroinflammation through the PTGS2/PGE 2 pathway. Notably, treatment with the ferroptosis inhibitor deferoxamine effectively mitigates PRV-induced ferroptosis, reduces viral titers in mouse brains, and alleviates viral encephalitis. In conclusion, our study reveals the critical role of ferroptosis in PRV-induced viral encephalitis, providing therapeutic insights for treating PRV-associated neurological diseases.